2019
DOI: 10.1038/s41551-019-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput, label-free, single-cell photoacoustic microscopy of intratumoral metabolic heterogeneity

Abstract: Intratumoral heterogeneity, which is manifested in almost all of the hallmarks of cancer, including the significantly altered metabolic profiles of cancer cells, represents a challenge to effective cancer therapy. High-throughput measurements of the metabolism of individual cancer cells would allow direct visualization and quantification of intratumoral metabolic heterogeneity, yet the throughputs of current measurement techniques are limited to about 120 cells per hour. Here, we show that single-cell photoaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…) may prove particularly beneficial to the discovery of new mechanisms and the identification of metabolic heterogeneity associated with pathology (Hai et al . )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) may prove particularly beneficial to the discovery of new mechanisms and the identification of metabolic heterogeneity associated with pathology (Hai et al . )…”
Section: Discussionmentioning
confidence: 99%
“…Using primary cell cultures from muscle and brain tissues, we further demonstrated how single-cell applications of mitoRACE can provide a novel approach to evaluating metabolism in specific subgroups of cells within complex cell populations. The combination of single-cell functional measures such as mitoRACE with single-cell sequencing technologies (Tang et al 2009) may prove particularly beneficial to the discovery of new mechanisms and the identification of metabolic heterogeneity associated with pathology (Hai et al 2019) While the structure-function relationships of mitochondrial networks are not completely understood, recent studies have found that subcellular differences in mitochondrial morphology (Glancy et al 2015), connectivity (Glancy et al 2015Bleck et al 2018) and interactions with other organelles (Benador et al 2018;Bleck et al 2018) are associated with intracellular differences in mitochondrial function. Therefore, the development of new metabolic imaging techniques that provide spatial and temporal information at the scales of mitochondrial function (microns and seconds, respectively) is critical to understanding the relationships between cell topography, mitochondrial morphology and the subcellular specialization of mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…For 25 years, PA imaging has been an active area and is now one of the hottest topics in biomedical optics. PA tomography (PAT) and microscopy (PAM) have numerous diagnostic applications [9][10][11], providing both endogenous [12][13][14][15] and exogenous molecular contrast in structural and functional images [15][16][17]. In particular, PA spectroscopy has produced functional images in the brain and heart [10,[18][19][20], and molecular images using the unique spectra of nanoengineered contrast agents [16,[20][21][22].…”
Section: Mainmentioning
confidence: 99%
“…The needle spectrum projection (Fig. 4 -upper right)clearly presents the needle with few artifacts 14. The middle row ofFig.4bshows PA images after injection.…”
mentioning
confidence: 95%
“…Photo-or optoacoustic (OA) imaging combines optical contrast with ultrasound resolution, enabling high-resolution, real-time in vivo imaging well beyond the 1 mm penetration depth typical of microscopy methods 1,2 . OA already has provided intriguing insights into tumor heterogeneity 3 , neuronal dynamics 4 , psoriasis 5 and brown fat metabolism 6 based on endogenous contrast from hemoglobin and lipids 7,8 . This is complemented by theranostic research 9,10 and clinical application 11 e.g.…”
Section: Introductionmentioning
confidence: 99%